Adaptation of The Scenario Test for Greek‐speaking people with aphasia: A reliability and validity study - Charalambous, Marina; Phylactou, Phivos; Elriz, Thekla; Psychogios, Loukia; Annoni, Jean-Marie; Kambanaros, Maria (My University, 2022)
Background Evidence-based assessments for people with aphasia (PWA) in Greek are predominantly impairment based. Functional communication (FC) is usually underreported and neglected by clinicians. This study explores the adaptation and psychometric testing of the Greek (GR) version of The Scenario Test. The test assesses the everyday FC of PWA in an interactive multimodal communication setting. Aims To determine the reliability and validity of The Scenario Test-GR and discuss its clinical value. Methods & Procedures The Scenario Test-GR was administered to 54 people with chronic stroke (6+ months post-stroke): 32 PWA and 22 stroke survivors without aphasia. Participants were recruited from Greece and Cyprus. All measures were administered in an interview format. Standard psychometric criteria were applied to evaluate reliability (internal consistency, test–retest, and interrater reliability) and validity (construct and known-groups validity) of The Scenario Test-GR. Outcomes & Results The Scenario Test-GR shows high levels of reliability and validity. High scores of internal consistency (Cronbach's α = 0.95), test–retest reliability (intra-class coefficients (ICC) = 0.99), and interrater reliability (ICC = 0.99) were found. Interrater agreement in scores on individual items ranged from good to excellent levels of agreement. Correlations with a tool measuring language function in aphasia, a measure of FC, two instruments examining the psychosocial impact of aphasia and a tool measuring non-verbal cognitive skills revealed good convergent validity (all ps < 0.05). Results showed good known-groups validity (Mann–Whitney U = 96.5, p < 0.001), with significantly higher scores for participants without aphasia compared with those with aphasia. Conclusions & Implications The psychometric qualities of The Scenario Test-GR support the reliability and validity of the tool for the assessment of FC in Greek-speaking PWA. The test can be used to assess multimodal FC, promote aphasia rehabilitation goal-setting at the activity and participation levels, and be used as an outcome measure of everyday communication abilities.
Keywords: The Scenario Test-GR; Functional communication assessment; People with aphasia (PWA); Tool validation